2018
DOI: 10.1002/fam.2507
|View full text |Cite
|
Sign up to set email alerts
|

Fire safety of thermoplastic polyurethane based on pyromellitic dianhydride

Abstract: Summary In this paper, pyromellitic dianhydride (PMDA) was firstly used as fire safety agent for thermoplastic polyurethane (TPU). And, the fire safety improvement of PMDA in TPU was intensively investigated by limiting oxygen index (LOI), smoke density test (SDT), cone calorimeter test, and thermogravimetric/infrared spectroscopy, respectively. It has been found that PMDA could significantly improve the ignition level, and the LOI value increase to 28.5% when 8.0 wt% PMDA was incorporated into TPU; PMDA also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Wang et al have studied the fire safety of the thermoplastic polyurethane based on pyromellitic dianhydride. 17 It has proved that pyromellitic dianhydride has good flame retardancy for TPU. However, pyromellitic dianhydride is toxic, which limits its application in the field of flameretardant TPU.…”
mentioning
confidence: 99%
“…Wang et al have studied the fire safety of the thermoplastic polyurethane based on pyromellitic dianhydride. 17 It has proved that pyromellitic dianhydride has good flame retardancy for TPU. However, pyromellitic dianhydride is toxic, which limits its application in the field of flameretardant TPU.…”
mentioning
confidence: 99%
“…The parameters such as SPR, TSP, total smoke release (TSR) and smoke factor (SF) were used to further characterize the smoke release during the combustion process of the composites. 35 The correlation curves are shown in Fig. 5.…”
Section: Combustion Performance Of Rpuf and Flame Retardant Rpuf Comp...mentioning
confidence: 99%
“…As a new type of flame retardant, acid anhydride displays excellent properties, such as excellent dimensional stability, thermal stability, and thermo‐oxidative stability 26,27 . In the flame‐retardant polymer field, it is reported that Jiao et.al have studied the flame retardancy of TPU based on pyromellitic dianhydride and the results show there is an indeed considerable positive effect on the flame retardancy 28 . However, pyromellitic dianhydride is toxic and has been limited in many applications.…”
Section: Introductionmentioning
confidence: 99%